2008
DOI: 10.1152/ajpheart.01206.2007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and impaired functional vasodilation in obese Zucker rats

Abstract: Individuals with metabolic syndrome exhibit insulin resistance and an attenuated functional vasodilatory response to exercise. We have shown that impaired functional vasodilation in obese Zucker rats (OZRs) is associated with enhanced thromboxane receptor (TP)-mediated vasoconstriction. We hypothesized that insulin resistance, hyperglycemia/hyperlipidemia, and the resultant ROS are responsible for the increased TP-mediated vasoconstriction in OZRs, resulting in impaired functional vasodilation. Eleven-week-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
65
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 59 publications
13
65
1
2
Order By: Relevance
“…Essentially, this may act as a "dampener" of entire microvascular networks and further constraint on the reactivity of the entire network rather than the distal microcirculation (as appears to be the case for NO bioavailability). Evidence from other research groups has provided support for this conjecture, demonstrating the impact of elevated TxA 2 activity to blunt agonist-induced and func- tional hyperemic responses within blood-perfused in situ microvascular networks (32,61,62). A similar outcome on reactivity throughout the network may follow from the graded increase in myogenic activation with elevated PVD risk.…”
Section: H499mentioning
confidence: 85%
See 1 more Smart Citation
“…Essentially, this may act as a "dampener" of entire microvascular networks and further constraint on the reactivity of the entire network rather than the distal microcirculation (as appears to be the case for NO bioavailability). Evidence from other research groups has provided support for this conjecture, demonstrating the impact of elevated TxA 2 activity to blunt agonist-induced and func- tional hyperemic responses within blood-perfused in situ microvascular networks (32,61,62). A similar outcome on reactivity throughout the network may follow from the graded increase in myogenic activation with elevated PVD risk.…”
Section: H499mentioning
confidence: 85%
“…The OZR is a model of significant PVD risk (in the absence of significant atherosclerosis), and previous results have identified a series of vasculopathies and contributing mechanisms that can impair skeletal muscle perfusion and performance (20,24,61,62). Going forward, recent studies have shed new light on microvascular dysfunction itself that may represent a more accurate predictor of poor outcomes in OZR than has been available previously.…”
Section: Linking Peripheral Vascular Disease (Pvd) Risk To Integratedmentioning
confidence: 99%
“…With continued hyperphagia, OZR become progressively insulin-resistant, dyslipidemic (hypercholesterolemia and severe hypertriglyceridemia) and moderately hypertensive (5, 18). As such, the OZR represents a complete model of the metabolic syndrome and, owing to the origin in a chronic excess caloric intake, an appropriate and relevant model for the human condition.Previous study from our laboratory and by others has demonstrated that multiple relevant pathways of both dilator and constrictor reactivity are altered in OZR with development of the metabolic syndrome, and this can contribute to an impaired ability to effectively match skeletal muscle perfusion with metabolic demand (10,11,34,35,36). Among these impacted pathways are those of endothelium-dependent origin, such as wall shear rate (3, 15), reduced PO 2 (16,17), and an array of pharmacological challenges, including acetylcholine (15) and arachidonic acid (17,(35)(36)(37).…”
mentioning
confidence: 98%
“…One attractive attribute of tempol is its ability to penetrate cell membranes and hence react with ROS both intracellularly and extracellularly, as well as within important organelles such as the mitochondria (Simonsen et al 2009). Tempol has been shown to improve acetylcholineand arachidonic acid-induced relaxation in skeletal muscle arteries and in coronary arteries from diabetic animals (Gao et al 2007;Xiang et al 2008). Furthermore, in an in vivo one-kidney one-clip hypertensive rat model, tempol improved endothelial function in small arteries exposed to high blood pressure (Christensen et al 2007).…”
Section: Sod Mimeticsmentioning
confidence: 99%